Studi Kepatuhan Dan Faktor Yang Mempengaruhi Pelaksanaan Sop Pengelolaan Limbah Patologis Laboratorium Patologi Anatomi - Icha Pradana Vinatasari; Yuyun Nailufar; Muhammad Khakim Abdillah (Journal of Innovation Research and Knowledge, 2026)
An anatomical pathology laboratory is a healthcare laboratory that plays an important role in supporting the diagnosis of various diseases, including cancer. However, all processes carried out in an anatomical pathology laboratory have the potential to pose risks to personnel and the environment if pathological waste is not managed in accordance with established procedures. This study aimed to determine the management of pathological waste and the level of staff compliance in pathological waste management at the Anatomical Pathology Laboratory of PKU Muhammadiyah Yogyakarta Hospital. This study employed a descriptive observational research design. The results showed that pathological waste management at the Anatomical Pathology Laboratory of PKU Muhammadiyah Yogyakarta Hospital generally complied with the provisions stipulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 7 of 2019, with a high level of staff compliance. Nevertheless, challenges were still identified regarding the storage period of pathological waste, which exceeded the prescribed time limit before transportation by a licensed third-party waste management company. Therefore, evaluation of the waste transportation schedule and regular monitoring are necessary to ensure that all stages of pathological waste management remain in accordance with applicable regulations.